Discussion: Effect of Corrugated Roughness on Developed Laminar Flow in Microtubes, (Duan, Z. and Muzychka, y. M., 2008 Asme Trans. J. Fluids Eng., 130 P. 031102 - Siginer, D (2012)
Sin Editorial Disponible